GOODS RETURN COSTS IN PARCEL COURIER SERVICES: A SHARIA ECONOMIC LAW PERSPECTIVE - Ubaidillah, Ubaidillah; Susanti, Ika; Hanip, Abdul; Nurjannah, Feby; Alfianto, Alfianto; Arifin, Mohammad Samsul (AL-IQTISHADIYAH : EKONOMI SYARIAH DAN HUKUM EKONOMI SYARIAH, 2025)
The phenomenon of applying return fees courier services in Bondowoso District has become a significant issue due to procedural uncertainty and potential injustice for consumers, particularly from the perspective of Sharia Economic Law. This research addresses two problems: (1) how is the practice of applying return fees courier services in Bondowoso District, and (2) how does Sharia Economic Law analyze this practice. The study aims to describe the practice of return fees and to analyze its compliance with the principles of ijarah and ju’alah contracts. A descriptive qualitative method with a case study approach was employed, using in-depth interviews, field observations, and documentation as data collection techniques. The research subjects consisted of couriers, the hub manager, and customers who had experienced returns. The findings reveal that return fees are generally charged when goods are rejected upon delivery, opened or damaged, or when the return process is carried out outside the application procedure. This practice does not entirely originate from the company’s official policy but rather from couriers’ personal initiatives. From the perspective of Sharia Economic Law, return fees can be justified as ijarah if there is a clear mutual agreement, but they have the potential to harm consumers if applied unilaterally.